2013
DOI: 10.1128/jb.01095-13
|View full text |Cite
|
Sign up to set email alerts
|

Identification of YidC Residues That Define Interactions with the Sec Apparatus

Abstract: In bacteria, a subset of membrane proteins insert into the membrane via the Sec apparatus with the assistance of the widely conserved essential membrane protein insertase YidC. After threading into the SecYEG translocon, transmembrane segments of nascent proteins are thought to exit the translocon via a lateral gate in SecY, where YidC facilitates their transfer into the lipid bilayer. Interactions between YidC and components of the Sec apparatus are critical to its function. The first periplasmic loop of YidC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…3c). The resulting proximity of the YidC TMD to SecDF is supported by recent independent screening and complementation experiments31. The YidC TMD was suggested to facilitate membrane-protein insertion, borne out by cross-linking between nascent TM-helices successively to SecY, lipids and finally to YidC10, including YidC-TM332.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…3c). The resulting proximity of the YidC TMD to SecDF is supported by recent independent screening and complementation experiments31. The YidC TMD was suggested to facilitate membrane-protein insertion, borne out by cross-linking between nascent TM-helices successively to SecY, lipids and finally to YidC10, including YidC-TM332.…”
Section: Resultsmentioning
confidence: 61%
“…Here, we combined a range of biophysical data to provide mechanistic and structural insights into the HTL membrane protein complex in an integrative approach. Based on the SANS data, EM volumes, subunit localization experiments and available biochemical data345122731 we present a quasi-atomic model of HTL and a working model for HTL function in translocation into and across the membrane and membrane protein folding (Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
“…The sequence analysis (see Table S1 in the supplemental material) showed that each of the menadione-auxotrophic SCVs carried a mutation in one of the menadione biosynthesis genes ( menA , menB , or menE ) and that each of the hemin-auxotrophic SCVs carried a mutation in one of the hemin biosynthesis genes ( hemB , hemC , hemD , hemE , or hemH ). The single nonauxotrophic SCV carried mutations in qoxB , oxaA , srrA , and ftsQ , genes that are involved in respiration or cell division ( 26 31 ), possibly explaining the SCV phenotype of this mutant. The median kanamycin MIC of the 26 mutant strains is 48 mg/liter ( Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Additional residues in this or other regions may also be important for the YidC and SecY interaction. Recently, Li et al (75) discovered Gly-355 in TM2 and Met-471 in TM4 of the E. coli YidC to be important for YidC-SecY interaction using a synthetic lethal screen. It has been hypothesized that the interaction of YidC with SecYEG is facilitated by SecDFYajC (76).…”
Section: Yidc Familymentioning
confidence: 99%